1998
DOI: 10.1016/s0304-3959(97)00199-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the perception of noxious experimental stimuli: a meta-analysis

Abstract: Fillingim and Maixner (Fillingim, R.B. and Maixner, W., Pain Forum, 4(4) (1995) 209-221) recently reviewed the body of literature examining possible sex differences in responses to experimentally induced noxious stimulation. Using a 'box score' methodology, they concluded the literature supports sex differences in response to noxious stimuli, with females displaying greater sensitivity. However, Berkley (Berkley, K.J., Pain Forum, 4(4) (1995) 225-227) suggested the failure of a number of studies to reach stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

67
526
13
27

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 973 publications
(647 citation statements)
references
References 23 publications
67
526
13
27
Order By: Relevance
“…Previous studies have also reported sex differences in pain experience 35,36 . Compared with men, women usually reported more frequent, severe, and persisting pain 36 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies have also reported sex differences in pain experience 35,36 . Compared with men, women usually reported more frequent, severe, and persisting pain 36 .…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have also reported sex differences in pain experience 35,36 . Compared with men, women usually reported more frequent, severe, and persisting pain 36 . A study reported differences in central pain processing, including the magnitudes and locations of ÎŒ-opioid system activation, between men and women 37 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other studies have also demonstrated that women are more sensitive to pain and more inclined to report greater pain in relation to experimentally controlled muscle pain conditions 24,25 . On the other hand, no gender differences have been found in relation to the development of delayed-onset muscle soreness in the neck and shoulder muscles 26 .…”
Section: Discussionmentioning
confidence: 94%
“…[1][2][3][4] The discovery that the circulating levels of sex hormones (SH), especially estrogen E2 and progesterone P2, besides the reproductive 8 and cardioprotective 9 roles, can exercise modulatory effects on the neuronal functions and alter the superficial cutaneous sensitivity 1,2 , gave rise to intriguing questions about the parameters of conformation/therapeutic modulation in analgesia in both genders, particularly in associations with thermal resources. [5][6][7][8][9][10][11] Considering that transcutaneous electrical nerve stimulation (TENS) appears as one of the most reliable and effective non-pharmacological resources for analgesia [3][4][5][6][7][10][11][12][13][14][15] , it became worth investigating the variations of the NSS between genders, and whether previous changes in skin temperature induced by heating/cooling would interfere in the adjustment/peripheral control of the NSS. Recently, experimental and clinical investigations showed that there are differences in the perception of the nociceptive stimulus, in the pain tolerance threshold and in cutaneous sensitivity to electrical stimuli between genders.…”
Section: Introductionmentioning
confidence: 99%